2020
DOI: 10.3390/ijms21238927
|View full text |Cite
|
Sign up to set email alerts
|

The Predicted Functional Compartmentation of Rice Terpenoid Metabolism by Trans-Prenyltransferase Structural Analysis, Expression and Localization

Abstract: Most terpenoids are derived from the basic terpene skeletons of geranyl pyrophosphate (GPP, C10), farnesyl-PP (FPP, C15) and geranylgeranyl-PP (GGPP, C20). The trans-prenyltransferases (PTs) mediate the sequential head-to-tail condensation of an isopentenyl-PP (C5) with allylic substrates. The in silico structural comparative analyses of rice trans-PTs with 136 plant trans-PT genes allowed twelve rice PTs to be identified as GGPS_LSU (OsGGPS1), homomeric G(G)PS (OsGPS) and GGPS_SSU-II (OsGRP) in Group I; two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…It was found that VvGGPPS (VIT_205s0020g01240) was clustered in the same clade as the other five protein sequences for which the subcellular localization was experimentally demonstrated (Supplementary Figure S7). The target VvGGPPS in this study presented the shortest distance from the rice XP 015647986 and tomato Solyc11g011240 sequences, both of which have been experimentally shown to be in chloroplasts (Zhou et al, 2017;You et al, 2020;Zhou and Pichersky, 2020;Barja et al, 2021). Chloroplasts are a type of plastid.…”
Section: Functional Validation Of Vvggpps In Transient Expression Systemmentioning
confidence: 54%
“…It was found that VvGGPPS (VIT_205s0020g01240) was clustered in the same clade as the other five protein sequences for which the subcellular localization was experimentally demonstrated (Supplementary Figure S7). The target VvGGPPS in this study presented the shortest distance from the rice XP 015647986 and tomato Solyc11g011240 sequences, both of which have been experimentally shown to be in chloroplasts (Zhou et al, 2017;You et al, 2020;Zhou and Pichersky, 2020;Barja et al, 2021). Chloroplasts are a type of plastid.…”
Section: Functional Validation Of Vvggpps In Transient Expression Systemmentioning
confidence: 54%
“…chinensis genome comprised seven complete RcTPTs , indicating that the number of TPTs in R . chinensis is less than those reported in Arabidopsis thaliana (16), tomato (10), Cinnamomum camphora (10), and Oryza sativa (12), and more than or equal to that in Chlamydomonas reinhardtii (4) and Physcomitrella patens (7) ( Table S5 ) [ 25 , 28 , 58 ]. Unlike the TPT gene family in Cinnamomum camphora (Lauraceae) that has segmentally duplicated TPT genes [ 28 ], no such TPT genes were observed in the genome of R .…”
Section: Discussionmentioning
confidence: 87%
“…GGPP synthase (GGPPS) enzymes generate GGPP by three sequential IPP condensation steps to DMAPP, via GPP and finally FPP. Consistent with the requirement of GGPP in multiple locations and growth stages to ensure proper development and response to environmental challenges, plant genomes have retained families of differentially expressed genes encoding GGPPS isoforms that interact with specific protein partners and localize to particular cell compartments, including cytosol, plastids, mitochondria, and endoplasmic reticulum (Barja et al 2021;Beck et al 2013;Coman et al 2014;Ruiz-Sola et al 2016b;Wang and Dixon 2009;Wang et al 2018;You et al 2020;Zhou and Pichersky 2020;Zhou et al 2017). Multiple copies of phylogenetically related (i.e., homologous) GGPPS-encoding genes that result from duplication events involving individual genes, chromosomal segments, or entire genomes are referred to as paralogs (in the same species) and orthologs (in different species).…”
Section: Ggpp Synthasesmentioning
confidence: 98%
“…GFP fusions of OsGGPPS1, OsGPPS and OsSSU-II proteins were targeted to chloroplasts (Fig. 1) (You et al 2020;Zhou et al 2017). Interestingly, OsSSU-II was found to recruit OsGGPPS1 from the chloroplast stroma to the thylakoid membranes, directing it to a large protein complex containing GGR and other components of the chlorophyll biosynthetic pathway, such as the light-harvesting-like protein LIL3 and the chlorophyll synthase CHLG (Fig.…”
Section: Ricementioning
confidence: 99%
See 1 more Smart Citation